О происхождении аномальнoй нумерации чтений после Пятидесятницы в сербском полноапракосном евангелии No. 8 Хиландарского монастыря - Юрьевич Темчин, Сергей (Slavistica Vilnensis, 2000)
This paper presents an explanation of the anomalous numbering of the lections after Pentecost in the Serbian long lectionary Gospel No 8 from the Hilandar Monastery (Hil. 8). Usually the weeks after Pentecost are numbered continuously from 1 to 17, but in Hil. 8 this liturgical cycle is divided into two parts with two separate numberings: 1–11 and 1–6. This division does not occur in other Slavic gospel lectionaries. The Gospel of St. Matthew is generally read during the liturgical cycle after Pentecost, with the exception of the weekday lections for the last six weeks, which are taken from St. Mark. This shift from Matthew to Mark was so significant to the scribe of Hil. 8 that he decided to emphasize it by introducing a new numbering of the weeks. Such an attitude indicates that the scribe must have been used to dealing with the liturgical tetraevangelion (in which the four Gospels are clearly separated) and not with the lectionary Gospel, and sheds some light on the geographical distribution of these two structural types of gospels.